An evaluation of a psychoeducation programme for emotion identification and expression in individuals diagnosed with schizophrenia - ÜNSAL, GÜL (WILEY, 2020)
The inability of individuals diagnosed with schizophrenia to recognize facial expressions is an important issue that has an impact on social functioning. This study was conducted to determine the effects of a psychoeducation programme for emotion identification and expression in those diagnosed with schizophrenia on their ability to identify and discriminate between emotions and social functionality. This quasi-experimental study (pretest-post-test, with control group) comprised an intervention (21) and a control (21) group conducted with individuals diagnosed with schizophrenia. A 10-week psychoeducation programme was offered to the intervention group. Measuring instruments were administered to the groups before the intervention, after the intervention, and 3 months after that. The measuring instruments consisted of a personal information form, the Facial Emotion Identification Test, Facial Emotion Discrimination Test, and Personal and Social Performance Scale. The data were analysed using the 'two-way repeated measures analysis of variance'. The TREND method was used for reporting. In the first measurements taken after the psychoeducation programme, a significant difference was found between the two groups in terms of their 'Facial Emotion Identification Test' and 'Personal and Social Performance Scale' mean scores. In the measurements taken 3 months after the psychoeducation programme, this difference had disappeared. The psychoeducation programme is an effective programme that makes recognition of facially expressed emotions possible and increases the social functioning of patients.
Keywords: facial expression; facial recognition; psychiatric nursing; psychoeducation; schizophrenia; AFFECT-RECOGNITION; SOCIAL COGNITION; INTERVENTION; RELIABILITY; PERCEPTION; DEFICITS; VERSION